The sustainability of hospital care in the Netherlands from a labour market perspective: A time series analysis of the Baumol effect between 2000 and 2021 - Jos L. T. Blank; Alex A. S. van Heezik (Economies, 2024)
In this paper, we focus on the sustainability of hospital care in The Netherlands from a labour market perspective. The continued increase in the demand for hospital care and the subsequent growth in the demand for hospital labour can cause permanent shortages of medical and nursing personnel, but can also affect labour conditions in other sectors of the economy. We analyse how the hospital sector put pressure on the labour market between 2000 and 2021 by applying a regression analysis to the share of hospital labour costs in the total economy on hospital production, wages and technical change. From the raw data, we observe a modest growth in hospital production over the whole research period. Strikingly, hospital wages underwent explosive growth compared to wages in other sectors of the economy in the same timeframe, seemingly disproving the hypothesis that hospital wages follow wages in other sectors. A worrisome result comes from the estimated Baumol parameter, which indicates that productivity growth in the hospital sector lagged significantly behind other sectors. This implies that the hospital sector, aside from developments in hospital care demand and hospital wages, is also causing a serious problem because of a low or negative productivity change. At this rate, we will stumble into the situation that the pressure of hospitals on the Dutch labour force will be doubled in the next decades. To avoid this situation, severe measures need to be taken, such as implementing incentives and sanctions to improve productivity.
Keywords: 330; time series; Baumol's disease; hospital care; labour demand; labour productivity; wages